2012
DOI: 10.1016/j.physbeh.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Isolation rearing attenuates social interaction-induced expression of immediate early gene protein products in the medial prefrontal cortex of male and female rats

Abstract: Early life adversity and stress in humans has been related to a number of psychological disorders including anxiety, depression, and addiction. The present study used isolation rearing, a well-characterized animal model of early life adversity, to examine its effects on social behavior and immediate early gene (IEG) expression produced by exposure to a novel social experience. Male and female rats were housed in same-sex groups or in isolation for 4 weeks beginning at weaning and were tested during late adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
77
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 74 publications
12
77
4
1
Order By: Relevance
“…This begs the question of the exact contribution of PrL, IL, and MO/VO in social play behavior, given that their inactivation produces comparable reductions in social play. Interestingly, cellular activation studies have found similar patterns of activity of PrL and IL neurons during social behavior in late adolescent rats (Wall et al, 2012) and during sexual behavior in adult rats (Balfour et al, 2006). Consistent with this, we have recently found comparable increases in c-fos expression in PrL, IL, MO, and VO after social play, although the magnitude of the effect differed somewhat between these regions (Van Kerkhof et al, 2013).…”
Section: Importance Of the Pfc For Social Play Behaviorsupporting
confidence: 86%
“…This begs the question of the exact contribution of PrL, IL, and MO/VO in social play behavior, given that their inactivation produces comparable reductions in social play. Interestingly, cellular activation studies have found similar patterns of activity of PrL and IL neurons during social behavior in late adolescent rats (Wall et al, 2012) and during sexual behavior in adult rats (Balfour et al, 2006). Consistent with this, we have recently found comparable increases in c-fos expression in PrL, IL, MO, and VO after social play, although the magnitude of the effect differed somewhat between these regions (Van Kerkhof et al, 2013).…”
Section: Importance Of the Pfc For Social Play Behaviorsupporting
confidence: 86%
“…Thus, it is possible that loss of M 1 -mediated mLTD at the hippocampo-PFC synapse plays a major role in regulating PFC activation by hippocampal afferents under normal conditions, and that loss of this function contributes to the increased activation of the PFC and resultant behavioral outcomes of dysfunctional recognition memory and social interaction in this rodent model. As normal PFC function is essential for both social interaction (Elliott et al, 2012;Shah and Treit, 2003;Wall et al, 2012) and recognition memory (Bekinschtein and Weisstaub, 2014;Watson et al, 2012) in rodents, this study provides the first direct evidence for a potential role of impaired M 1 -mediated mLTD in PFC as an underlying cause of these behavioral deficits.…”
Section: Role Of M 1 Pam In Pcp-treated Micementioning
confidence: 70%
“…Rats were used for experiments after 4-5 weeks (P50-60 postadolescents), or at intermediate time points, as described below. Several studies indicate that social behavior in males may be more sensitive to postweaning social isolation (Ferdman et al, 2007;Wall et al, 2012;Ahern et al, 2016). Therefore, males were the focus of the current study.…”
Section: Methodsmentioning
confidence: 99%